Hubungan Kualitas Tidur dan Tingkat Kemandirian Activity of Daily Living dengan Risiko Jatuh Pada Lanjut Usia di Puskesmas Simpang IV Sipin Kota Jambi - Mashudi Mashudi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The census of the population of 2010 years old aged 60 years and above is ± 18 million people or 7.6% of the total population. In 2014, the population was 18.781 million. The increasing number of elderly people in Indonesia has impacted the increasing problems in elderly groups. Various limitations due to decreased function and the anatomical changes in the body as well as disease processes increase the risk of elderly falls. This study uses a cross sectional analytical method of analytics survey, aims to determine the relationship of sleep quality and the level of self-reliance in the Activity of Daily Living with the risk of falling in the elderly at the Puskesmas Sipin Simpang IV city Center Jambi. Data collection using questionnaires and observation sheets. Sample amount of 95 elderly people with accidental sampling technique. Data analysis using Chi-square test. The results of the chi-square analysis have a meaningful relationship between the sleep and the risk of falling (p-value = 0.000) and there is a meaningful relationship between the degree of self-reliance in the Activity of Daily Living (ADL) with a falling risk (p-value = 0.007). Nurses can educate the elderly how to prevent falling by teaching safe techniques to move, precisely pick up, bend down, avoid hasty or sudden movements, proper activity time, and the use of The correct medication.